Todo es hermoso en su lugar: El misterio de la belleza en Agustín de Hipona = Abweichender Titel:"All Things Beautiful in their Place" : Augustine and the Mystery of Beauty - Gómez García, Enrique (Cauriensia, 2025)
The Christian tradition has developed three principal paths to the experience of God: the ontological-cosmological path, the anthropological-transcendental path and the historical path. Nonetheless, one must not overlook another route towards God; one that synthesises the aforementioned approaches: the via pulchritudinis. This article seeks to trace the significance of aesthetics in the thought of Augustine of Hippo, thereby presenting him as one of the foremost advocates of the way of beauty in the early Christian tradition. To this end, the study briefly engages with Augustine’s aesthetic principles, for apply them afterwards to concrete realities: God, creation, the human person, Christ, and even the presence of evil. In such application, philosophy is reinterpreted through the lens of faith; specifically, the faith of a convert.